Remarks on the Experimental Turn in the Study of Scalar Implicature, Part I. Issue 9 (September 2014) - Chemla, Emmanuel; Singh, Raj
Abstract (for Part I and Part II) There has been a recent 'experimental turn' in the study of scalar implicature, yielding important results concerning online processing and acquisition. This paper highlights some of these results and places them in the current theoretical context. We argue that there is sometimes a mismatch between theoretical and experimental studies, and we point out how some of these mismatches can be resolved. We furthermore highlight ways in which the current theoretical and experimental landscape is richer than is often assumed, and in light of this discussion, we offer some suggestions for what seem to us promising directions for the experimental turn to explore. The article is divided in two parts. Part I first presents the two dominant families of accounts of scalar implicature, the domain‐general Gricean account and the domain‐specific grammatical account. We try to separate the various components of these theories and connect them to relevant psycholinguistic predictions. Part II examines and reinterprets several prominent experimental results in light of the theoretical presentation proposed in the first part.